Minerals In The World Economy - Summary Of International Events Impacting The Minerals Economy In 1992 - Ivette E. Torres (The National Institute for Occupational Safety and Health (NIOSH), 1994)
Many significant events that began in 1990-91 continued to have a profound impact in the world minerals economy in 1992. The dissolution of the U.S.S.R. and the formal breakup of the Council for Mutual Economic Assistance (CMEA) had significant effects far beyond the geographic boundaries of Europe and Central Eurasia. CMEA's network of economic interdependence had relied on central planning, a variety of subsidies, and barter agreements that allowed its members to function without the pressures of productivity and efficiency. In the mineral sector, many decisions had been made based on the need for military planning and technology competition with the market economy world. Because of inexpensive oil available through subsidies and technology assistance from the former U.S.S.R., industries III CMEA member countries had been able to function and maintain production to supply minerals and materials required to support the policies of the central plan. In 1992, most of the former CMEA countries decreased their output of many minerals. In some cases, the network of production that had been in place was severed. Political and economic instability, destruction of infrastructure, and new priorities were affecting other mineral industries in the area. In late 1991, 15 independent countries replaced the U.S.S.R. and in early 1991 the former CMEA countries found themselves trying to adjust to the realities of economic independence and the need to compete with former allies for survival. Although 11 of the 15 former Soviet republics joined in the Commonwealth of Independent States (CIS) in December 1991, in 1992, individual economic needs exceeded the needs of the Commonwealth III importance. As a result, new mineral trade patterns emerged as minerals were used as a source of much needed capital.